Aktivitas Hard Adventure Di Gunung Batur Kintamani Bali - Widyawati, Veronica Sharen; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
This research discusses the potential of adventure tourism, especially in hard adventure activities on Mount Batur Kintamani Bali in providing both positive and negative environmental, social, and economic impacts to know what potential Mount Batur Kintamani Bali has by looking at its characteristics that are suitable for holding hard adventure activities. This research uses qualitative data. The data sources used include primary and secondary data. Data collection techniques in this research are interviews, observation, documentation, and literature study. The informant determination technique used is purposive sampling. The analysis technique used is qualitative descriptive. Data analysis in this research is SWOT analysis. Based on the results of the study, the condition of adventurous tourism in Mount Batur Kintamani Bali is a unique interest resource that is attractive to tourists looking for adventure and challenges in the wild. Mount Batur has now become good adventurous tourism from climbing Mount Batur as well as ATV (All-Terrain Vehicle), mountain biking, dirt bike, and Jeep car. This tourist destination has strong potential as an adventure tourism destination with extraordinary scenery. The suggestions in this study are in the level of supervision and guidance of tourism managers. Optimizing the level of promotion to increase the popularity of Mount Batur adventure tourism. By implementing these suggestions, it is hoped that adventure tourism on Mount Batur can continue to grow, provide good benefits for the local community, and continue to maintain the environmental quality and sustainability of Mount Batur tourist destinations. Keywords: Potential; Adventure Tourism; Tourism Impact